Acute kidney injury in idiopathic membranous nephropathy with nephrotic syndrome. Issue 1 (1st January 2021) - Chen, Tianxin; Zhou, Ying; Chen, Xinxin; Chen, Bo; Pan, Jingye
Abstract: Background and objectives: The impact of acute kidney injury (AKI) on the progression of renal function in idiopathic membranous nephropathy (iMN) with nephrotic syndrome (NS) patients have not yet been reported, we sought to investigate the incidence, clinical features and prognosis of AKI in iMN with NS patients and determine clinical predictors for progression from AKI to advanced chronic kidney disease (CKD) stage. Methods: We analyzed clinical and pathological data of iMN with NS patients retrospectively collected from Jan 2012 to Dec 2018. The primary renal endpoint was defined as persistent eGFR <45ml/min per 1.73 m 2 more than 3 months. Comparisons of survival without primary renal endpoint were performed by Kaplan-Meier curves and log-rank test. Univariate and multivariate Cox proportional hazard models were constructed to determine independent variables associated with primary renal endpoint . Results: 434 iMN with NS patients were enrolled. The incidence of AKI 1 stage, AKI 2 stage and AKI 3 stage was 23.1, 4.8 and 0.7% respectively. 66 (53.2%) patients with AKI had complete renal function recovery and 42 (33.9%) patients with AKI reached primary renal endpoint. Survival without primary renal endpoint was worse in AKI patients than No AKI patients (67.1 ± 5.3 and 43.7 ± 7.3% vs 99.5 ± 0.5 and 92.5 ± 4.2% at 2 and 4 years, p  < 0.001). AKI was independently associated with primary renal endpoint, with an adjusted hazard ratio(HR) of 25.1 (95%CI 7.7–82.1, p  < 0.001). Conclusions: AKI was usually mild and overlooked in iMN patients with NS, but it had a strong association with poor clinical outcomes and was an independent risk factor for CKD progression.